Rancang Bangun Sistem Jejaring Klaster Berbasis Web Menggunakan Metode Model View Controller - Suprihadi Suprihadi; Rini Kartika Hudiono; Lina Sinatra Wijaya (CCIT Journal, 2013)
Cluster in Indonesia particularly in the area of Central Java in 2010 totaled 150. Based on the results of the survey in Demak, Wonosobo and Pemalang, most Clusters does not yet have a website as a media product promotion and Cluster communication. Some Cluster already leverages media Blog and facebook but the media still do not meet the expected needs because media Blog and Facebook are not a media for product promotion. This is because the limitations of cost and the scarcity of skilled human resources information technology owned by the Cluster. Therefore, this research was conducted on the design and implementation of a web application that serves as a Networking System Cluster. System development method’s using the Prototype Model. Method of MVC (Model View Controller) is used in the implementation of the system, while technology programming using CodeIgniter Framework. As a result, the system is capable of providing the website for each Cluster are listed, so it can be used as a promotional media, publications and communication between Cluster members.